2015
DOI: 10.1161/atvbaha.115.305537
|View full text |Cite|
|
Sign up to set email alerts
|

Platelet Inhibitors Reduce Rupture in a Mouse Model of Established Abdominal Aortic Aneurysm

Abstract: Objective Rupture of abdominal aortic aneurysms (AAAs) causes a high morbidity and mortality in the elderly population. Platelet-rich thrombi form on the surface of aneurysms and may contribute to disease progression. In this study, we used a pharmacologic approach to examine a role of platelets in established aneurysms induced by angiotensin II (AngII) infusion into hypercholesterolemic mice. Approach and Results Administration of the platelet inhibitors aspirin (ASA) or clopidogrel bisulfate to established… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
82
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(85 citation statements)
references
References 62 publications
1
82
1
1
Order By: Relevance
“…The accelerated accumulation of platelets at the lesion site provides hemostatic protection initially, but, as the lesion progresses, platelets via production of proinflammatory mediators like PDGF could contribute to aneurysm formation. 26,27 Although platelets are the main source of PDGF, other cell types, including VSMCs, endothelial cells, and inflammatory cells, also produce this agent. 28,32,46 Therefore, the contribution of CYP1B1 to the expression of the four different isoforms of PDGF was assessed at the site of the lesion in Ang IIeinduced AAA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The accelerated accumulation of platelets at the lesion site provides hemostatic protection initially, but, as the lesion progresses, platelets via production of proinflammatory mediators like PDGF could contribute to aneurysm formation. 26,27 Although platelets are the main source of PDGF, other cell types, including VSMCs, endothelial cells, and inflammatory cells, also produce this agent. 28,32,46 Therefore, the contribution of CYP1B1 to the expression of the four different isoforms of PDGF was assessed at the site of the lesion in Ang IIeinduced AAA.…”
Section: Discussionmentioning
confidence: 99%
“…Since platelets also contribute to inflammation in AAA, 26 we determined the localization of CD62p þ -activated platelets in aortic sections from Apoe À/À / Cyp1b1 þ/þ mice treated with TMS and from Apoe À/À / Cyp1b1 À/À mice. Ang II infusion for 28 days increased the accumulation of F4/80 þ macrophages, CD3 þ T cells, and CD62p þ -activated platelets at the lesion site in the aortae of Apoe À/À /Cyp1b1 þ/þ mice but not in mice concurrently receiving TMS or in Apoe À/À /Cyp1b1 À/À mice ( Figure 2).…”
Section: Tms or Cyp1b1 Gene Disruption Prevents Aortic Inflammatory Cmentioning
confidence: 99%
“…[25] Blood was collected from the inferior vena cava and plasma prepared as previously described. [11,26]…”
Section: Methodsmentioning
confidence: 99%
“…5860 To extend insights into the contributions of platelets to AAA, Owens and colleagues studied the effects of platelet inhibitors, aspirin and clopidogrel, on established AAA in AngII-infused mice and found that inhibition of platelets profoundly reduced aortic rupture. 61 In addition to effects of platelets in thrombosis and AAA, thrombomodulin, a cofactor of thrombin, has also been reported to contribute to both calcium chloride-induced and AngII-induced AAA in mice. 62 Findings in these study implicate important roles of hemostatic factors in the development and progression of AAA.…”
Section: Abdominal Aortic Aneurysmsmentioning
confidence: 99%